Bis[4-(dimethyl-amino)-pyridinium] dibromidodichloridodimethyl-stannate(IV). - Lo, K.M.; Ng, Seik Weng (International Union of Crystallography, 2008)
The tin(IV) atom in the salt, (C(7)H(11)N(2))(2)[SnBr(2)(CH(3))(2)Cl(2)], lies on a center of inversion in a tetra-gonally compressed octa-hedron; the bromine atoms are disordered with the chlorine atoms, so that they appear to share the same site. The crystal structure is stabilized by N-H⋯Br hydrogen bonds.